Finland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1997)
This Selected Issues paper reviews some features of the labor market in Finland during the 1990s. In particular, it reviews patterns of employment and wage distribution across sectors. The paper describes the main regulatory features and formal structure of labor market arrangements: the wage negotiation process, employment legislation, income replacement regulations for the unemployed, and the recent changes in these areas introduced by the government. The paper also describes the structure of labor taxation, and reviews the theory and existing empirical evidence concerning the effects of taxation on labor market outcomes.